The effect of cocoa (Theobroma cacao L) on the basic color stability of thermoplastic nylon resin dentures - Naini, Amiyatun (Padjadjaran Journal of Dentistry, 2011)
Nylon thermoplastic resin is material of choice for the making of flexible. This denture do not use wire retention, but has the physical properties of water absorption. In the oral cavity, it will always be in contact with food and beverages consumed. One of the foods that are consumed by the public is chocolate. This study aimed to determine the effect of cocoa (Theobroma cacao L) on color stability of the thermoplastic nylon denture base. The study sample was thermoplastic nylon (valplast) with a size of 10x10x2 mm soaked in the chocolate solution for 7 and 14 days. As the control, the sample soaked with distilled water. The color testing stability used was densitometer. There were significant differences between the control group (distilled water) and the chocolate solution. This was due to dissolved components/tannin having a capillary flow diffusion into thermoplastic nylons that causing discoloration. The conclusion of this study, there was the effect of cocoa (Theobroma cacao L) against the color stability of the nylon thermoplastic denture base. The longer time of immersion of nylon thermoplastic the greater the change in color.